Pengembangan Etos Keguruan dalam Pendidikan Era Milenial - Abnisa, Almaydza Pratama (Indo-MathEdu Intellectuals Journal, 2023)
A strong teaching ethos is the foundation of all interactions and teaching that impact the younger generation in this linear era. This research highlights the important role of teacher ethos in supporting quality and sustainable education. Factors that shape the ethos of teaching include integrity, respect, commitment, and willingness to continue learning. When teachers adopt these values, they become role models who motivate students and create an inclusive, safe, and inspiring learning environment. The importance of continuous education and training for teachers to improve their skills and insights cannot be ignored in today's lilenial world. Teachers must remain relevant to developments in education and continue to develop as professionals. The development of teacher ethos has been successfully implemented, such as handling cases of academic violations with ethics and honesty, as well as teacher collaboration in improving student learning outcomes. The development of teacher ethos has been successfully implemented, such as handling cases of academic violations with ethics and honesty, as well as teacher collaboration in improving student learning outcomes.